2017
DOI: 10.18632/oncotarget.14608
|View full text |Cite
|
Sign up to set email alerts
|

Multiple biological functions of Twist1 in various cancers

Abstract: Twist1 is a well-known regulator of transcription during embryonic organogenesis in many species. In humans, Twist1 malfunction was first linked to Saethre-Chotzen syndrome and later identified to play an essential role in tumor initiation, stemness, angiogenesis, invasion, metastasis, and chemo-resistance in a variety of carcinomas, sarcomas, and hematological malignances. In this review, we will first focus on systematically elaborating the diverse pathological functions of Twist1 in various cancers, then de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
106
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(112 citation statements)
references
References 121 publications
6
106
0
Order By: Relevance
“…TW is a well-established master regulator of EMT in carcinoma (Qin et al, 2012;Zhao et al, 2017;Zhu et al, 2016), and loss of TW function has been shown to decrease tumorigenicity in lung carcinoma xenografts (Burns et al, 2013;Lv et al, 2015;Tran et al, 2012), but existing data on TW function in glioma is restricted to in vitro functional analysis or correlations of expression in human tissue samples with clinical features of malignancy or outcome (Elias et al, 2005;Mikheeva et al, 2010;Nordfors et al, 2015). The purposes of this study were to demonstrate the potential therapeutic relevance of targeting TW in human GBM and identify mechanisms downstream of TW.…”
Section: Discussionmentioning
confidence: 99%
“…TW is a well-established master regulator of EMT in carcinoma (Qin et al, 2012;Zhao et al, 2017;Zhu et al, 2016), and loss of TW function has been shown to decrease tumorigenicity in lung carcinoma xenografts (Burns et al, 2013;Lv et al, 2015;Tran et al, 2012), but existing data on TW function in glioma is restricted to in vitro functional analysis or correlations of expression in human tissue samples with clinical features of malignancy or outcome (Elias et al, 2005;Mikheeva et al, 2010;Nordfors et al, 2015). The purposes of this study were to demonstrate the potential therapeutic relevance of targeting TW in human GBM and identify mechanisms downstream of TW.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, TWIST1 may be a direct MYC transcriptional target [80]. Both TWIST1 and TGF-ÎČ1 are in turn, regulate by directly or indirectly binding to the hypoxia-response element (HRE) HIF-dependent [81].…”
Section: Neuroblastomamentioning
confidence: 99%
“…This finding contrasts with that of earlier studies in which Twist1 upregulation, as identified in numerous carcinomas, promoted neo-angiogenesis. 7 These distinct roles of Twist1 in tumor epithelial cells may be attributed to the different microenvironment found in solid tumors compared with the bone marrow HSC niche. More studies need to be performed to address this difference.…”
Section: Niche Twist1 Deficiency Impairs Hematopoietic Stem Cell Funcmentioning
confidence: 99%
“…The overexpression of Twist1 has been described as a poor prognostic factor in numerous epithelial-derived malignancies such as breast cancer, prostate cancer, colorectal cancer, bladder cancer, melanoma, hepatocellular carcinoma and neck carcinoma. 7 Twist1 has been found to be overexpressed in mononuclear cells from the bone marrow of patients with AML and chronic myeloid leukemia, 12 with a strong correlation between the expression of Twist1 and Bmi-1, an essential polycomb complex group with a fundamental role in the maintenance of leukemia stem cells. In fact, AML patients whose blasts overexpress Twist1 have a more aggressive clinical phenotype, with a good response to the cell cycle phase-specific agent cytarabine but not to the non-cell cycle phase-specific anthracycline, daunorubicin.…”
Section: Twist1 In Acute Myeloid Leukemiamentioning
confidence: 99%